Alignment of State Regulations With Breastfeeding and Beverage Best Practices for Childcare Centers and Family Childcare Homes, United States. (January 2021) - Lee, Danielle L.; Traseira, Raquel; Navarro, Sophia; Frost, Natasha; Benjamin-Neelon, Sara E.; Cradock, Angie L.; Hecht, Ken; Ritchie, Lorrene D.
Objectives: Childcare is an important setting for nutrition; nearly half of young children in the United States participate in licensed childcare, where they consume up to two-thirds of their daily dietary intake. We compared state regulations for childcare with best practices to support breastfeeding and healthy beverage provision. Methods: We reviewed regulations for childcare centers (centers) and family childcare homes (homes) in effect May–July 2016 and rated all 50 states for inclusion (1 = not included, 2 = partially included, 3 = fully included) of 12 breastfeeding and beverage best practices. We calculated average ratings for 6 practices specific to infants aged 0-11 months, 6 practices specific to children aged 1-6 years, and all 12 practices, by state and across all states. We assessed significant differences between centers and homes for each best practice by using McNemar–Bowker tests for symmetry, and we assessed differences across states by using paired student t tests. Results: States included best practices in regulations for centers more often than for homes. Average ratings (standard deviations) in regulations across all states were significantly higher in centers than in homes for infant best practices (2.1 [0.5] vs 1.8 [0.5], P < .001), child best practices (2.1 [0.6] vs 1.8 [0.6], P = .002), and all 12 best practices combined (2.1 [0.5] vs 1.8 [0.6], P < .001). Conclusions: Although best practices were more consistently included in regulations for centers than for homes, many state childcare regulations did not include best practices to support breastfeeding and the provision of healthy beverages. Findings can be used to inform efforts to improve regulations and to reduce differences between centers and homes.